Empowering Coffee Farmers Through Training on Diversification of Processed Cinnamon Coffee Products at UMKM Rizki Amalia: Pemberdayaan Petani Kopi Melalui Pelatihan Diversifikasi Produk Olahan Kopi Kayu Manis di UMKM Rizki Amalia - A. Hasdiansyah; Sriyanti Mustafa; Mughaffir Yunus; Ihwan Ridwan; Andi A. Mattunruang; Ilmar A. Achmad (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2023)
The coffee business is booming along with the growth of coffee shops, both large and small scale. This fact makes the coffee market more competitive, so coffee producers need to innovate and diversify more varied coffee preparations. The purpose of this empowerment is to encourage partners to present products that are different from the products that have been produced so far. This activity develops liquid cinnamon processed coffee which is a diversification of Rizki Amalia's MSME ground coffee products. This cinnamon coffee making training is based on the problem of high competitiveness between ground coffee producers in Enrekang. Black ground coffee producers and sellers have been widely spread in Enrekang district so that better innovation is needed to increase the selling value of coffee products. The results of this training contributed new knowledge and skills for Rizki Amalia MSME players in processing black ground coffee products combined with ground cinnamon. This activity is expected to make Rizki Amalia MSME products have a higher selling value than before. In the future, assistance to Rizki Amalia MSMEs will continue to provide training on developing digital-based product marketing.